Immunostimulatory Effect of Postbiotics Prepared from Phellinus linteus Mycelial Submerged Culture via Activation of Spleen and Peyer’s Patch in C3H/HeN Mice - Min Geun Suh; Hyun Young Shin; Eun-Jin Jeong; Gaeuleh Kim; Se Bin Jeong; Eun Ji Ha; Sang-Yong Choi; Sung-Kwon Moon; Kwang-Won Yu; Hyung-Joo Suh; Hoon Kim (Pharmaceuticals, 2022)
Medicinal mushrooms are an important natural resource promoting health benefits. Herein, Phellinus linteus mycelia were prepared under submerged cultivation, the mycelium-containing culture broth was extracted as a whole to obtain the postbiotic materials (PLME), and its effect on the immune system was evaluated in normal C3H/HeN mice. Oral administration of PLME for 4 weeks was well tolerated and safe. In the PLME-administered groups, in addition to the production of immunostimulatory cytokines, such as interferon gamma (IFN-γ), tumor necrosis factor-α (TNF-α), and interleukin 6 (IL-6), the mitogenic activity was significantly increased. PLME administration also significantly increased the levels of serum immunoglobulin G (IgG) and IgA in the small intestinal fluid and Peyer’s patches and enhanced Peyer’s patch-mediated bone marrow cell proliferation activity and cytokine production (IL-2, IL-6, and IFN-γ). Histomorphometric analyses showed an increase in immune cells in the spleen and small intestinal tissues of mice administered PLME, supporting the rationale for its immune system activation. PLME mainly contained neutral sugar (969.1 mg/g), comprising primarily of glucose as a monosaccharide unit. The β-glucan content was 88.5 mg/g. Data suggest that PLME effectively promote immune function by stimulating the systemic immune system through the spleen and intestinal immune tissues. PLME can thus be developed as a functional ingredient to enhance immune functions.